Training Models to Improve Human Resources Professionality Rafa Beauty Clinic - Taufiq, Josefa Vanina Winata; Purwadhi, Purwadhi; Handayani, Nining (ProBisnis : Jurnal Manajemen, 2025)
The era of globalization and the rapid development of the beauty industry demands the need for professional human resources in beauty clinics to be very important. The professionalism of human resources in beauty clinics includes aspects such as technical skills, knowledge of beauty procedures, communication skills, service ethics, and compliance with applicable safety standards and regulations. The purpose of this study was to determine the readiness of the training model and handling of obstacles to improve the professionalism of human resources at the Rafa Beauty Clinic. The research design was descriptive qualitative. Participants in this study were the leaders and employees of the Rafa Beauty Clinic. Data collection techniques used observation, interviews and documentation. The results showed that the Rafa Beauty Clinic chose the Kirkpatrik Training Model training model. The obstacles faced in training were the small training budget and the slowness of employees in understanding the training material. Efforts to overcome obstacles include increasing the allocation of training budget and periodic evaluation.